Development of virtual labs assisted by picture story book on material changes for 8th grade deaf students - Muhamad Bagus Setiawan; Ani Rusilowati; Budi Astuti (JPK (Jurnal Pendidikan Khusus), 2019)
The purpose of this research was to develop virtual labs learning media assisted with picture story book for deaf students. This research method is Research and Development (RD) with 3D models from 4D which include: define, design, and develop. Product trials are conducted at Ungaran state special school in the even semester of 2017/2018 school year. The subjects of the study were two deaf students at 8th grade Ungaran state special school. The results of the feasibility test of virtual labs and the picture story book obtained a feasibility percentage of virtual labs of 88.2% with very feasible criteria and the picture story book of 84.3% with feasible criteria. Then, the practicality test of virtual labs and the picture story book obtained a percentage of 85.7% and 88.1% with very practical criteria. Then, the results of the effectiveness test using effect size obtained values of 1.75 and 1.8 in the high category. Based on these data, it can be concluded that virtual labs learning media and the picture story book were feasible, practical, and effective to use in supporting the natural science learning process of deaf students.